Introduction of the concept of social responsibility in the activity of pharmaceutical organizations - N. О. Tkachenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
In respect that the social responsibility of business is employers’ voluntary contribution to the development of society, detailed study requires ethical issues, personal motives and other components of the formation of socially responsible behavior of the pharmacy’s subjects, taking into account the levels of its formation: personal - collective - public.